Dexamethasone Inhibits White Adipose Tissue Browning - Giordano, Alejandra (2024)
White adipose tissue (WAT) regulates energy balance through energy storage, adipokines secretion and the thermogenesis process. Beige adipocytes are responsible forWAT thermogenesis. They are generated by adipogenesis or transdifferentiation during cold or β3-adrenergic agonist stimulus through a process called browning. Browning has gained significant interest for to its preventive effect on obesity. Glucocorticoids (GCs) have several functions in WAT biology; however, their role in beige adipocyte generation and WAT browning is not fully understood. The aim of our study was to determine the effect of dexamethasone (DXM) on WAT thermogenesis. For this purpose, rats were treated with DXM at room temperature (RT) or cold conditions to determine different thermogenic markers. Furthermore, the effects of DXM on the adipogenic potential of beige precursors and on mature beige adipocytes were evaluated in vitro. Our results showed that DXM decreased UCP-1 mRNA and protein levels, mainly after cold exposure. In vitro studies showed that DXM decreased the expression of a beige precursor marker (Ebf2), affecting their ability to differentiate into beige adipocytes, and inhibited the thermogenic response of mature beige adipocytes (Ucp-1, Dio2 and Pgc1α gene expressions and mitochondrial respiration). Overall, our data strongly suggest that DXM can inhibit the thermogenic program of both retroperitoneal and inguinalWAT depots, an effect that could be exerted, at least partially, by inhibiting de novo cell generation and the thermogenic response in beige adipocytes.